Integrated Transcriptomics and Proteomics to Reveal Regulation Mechanism and Evolution of SmWRKY61 on Tanshinone Biosynthesis in Salvia miltiorrhiza and Salvia castanea - Chen, Yue; Wang, Yanting; Guo, Juan; Yang, Jian; Zhang, Xiaodan; Wang, Zixuan; Cheng, Ying; Du, Zewei; Qi, Zhechen; Huang, Yanbo; Dennis, Mans; Wei, Yukun; et al. (Frontiers in Plant Science, 2022)
Tanshinones are the main active compounds for treatment of cardiovascular and cerebrovascular diseases in Salvia species, but their contents are hugely different in species. For example, tanshinone IIA content in Salvia castanea Diels f. tomentosa Stib. is about 49 times higher than that in Salvia miltiorrhiza Bunge. The molecular mechanism responsible for this phenomenon remain largely unknown. To address this, we performed comparative transcriptomic and proteomic analyses of S. miltiorrhiza and S. castanea. A total of 296 genes in S. castanea and 125 genes in S. miltiorrhiza were high-expressed at both the transcriptional and proteome levels, including hormone signal regulation, fungus response genes, transcription factors and CYP450. Among these differentially expressed genes, the expression of SmWRKY61 was particularly high in S. castanea. Overexpression of SmWRKY61 in S. miltiorrhiza could significantly increase the content of tanshinone I and tanshinone IIA, which were 11.09 and 33.37 times of the control. Moreover, SmWRKY61 had a strong regulatory effect, elevating the expression levels of tanshinone pathway genes such as DXS2, CMK, HMGS2, CPS1, KSL1, KSL2, CYP76AH1 and CYP76AK3. For the WRKY family, 79 SmWRKYs were originally obtained and classified into three main groups. Collinearity analysis indicated a more specific extension of WRKY gene family in Salvia genus. In 55 Salvia species, only 37 species contained the WRKY61 sequence and high SmWRKY61 expression in some Salvia L. species was often accompanied by high tanshinone accumulation. Above results suggest that SmWRKY61 is a highly effective regulator of tanshinone accumulation and may be a key factor resulting in high tanshinone accumulation in S. castanea.